2014
DOI: 10.1007/s00345-014-1386-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel kidney segmentation system to describe tumour location for nephron-sparing surgery

Abstract: Kidney segmentation (KS) system is an objective and reproducible radiologic method of universally reporting tumour location according to 12 renal segments. By adding descriptive information on tumour characteristics in candidates for nephron-sparing surgery, this novel KS system could serve as an adjunct to current nephrometry systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Consequently, unclamped minimal-margin PN is optimally indicated for tumors located in the medial half of the kidney, including hilar, polar, and other medial locations. These correspond to the recently described anatomic kidney segments numbered 2, 4, 6, 8, 10, and 12 [16]. Future work is required to preoperatively identify the presence of a pseudocapsule and other tumor characteristics to personalize unclamped PN technique for tumor and patient features.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, unclamped minimal-margin PN is optimally indicated for tumors located in the medial half of the kidney, including hilar, polar, and other medial locations. These correspond to the recently described anatomic kidney segments numbered 2, 4, 6, 8, 10, and 12 [16]. Future work is required to preoperatively identify the presence of a pseudocapsule and other tumor characteristics to personalize unclamped PN technique for tumor and patient features.…”
Section: Discussionmentioning
confidence: 98%
“…2 In this setting, preoperative imaging with a standardized method to report tumor location and nephrometry scores is crucial for choosing the most appropriate technique. 3 In the current study, Tachibana et al showed the superiority of robotassisted PN in terms of surgical outcomes, including renal function and the preserved renal parenchymal volume. 4 Nevertheless, surgical outcomes and volume loss are only part of all the aspects involved in renal function outcomes.…”
Section: Editorial Commentmentioning
confidence: 57%
“…These goals can be reached by using tumor enucleation or minimal margin PN techniques and minimally ischemic or off‐clamp PN whenever feasible . In this setting, preoperative imaging with a standardized method to report tumor location and nephrometry scores is crucial for choosing the most appropriate technique . In the current study, Tachibana et al .…”
mentioning
confidence: 90%
“…The present study represents an early evaluation of this technology for paediatric patients with WT, which to our knowledge, has not been previously reported. Earlier studies have described manual segmentation techniques, developed for radiologists to accurately describe tumour location and provide tissue volume assessments . However, we effectively trained a program to recognize WT features from CT scan images and differentiate it from adjacent structures and surrounding parenchyma, with minimal supervision from clinical staff.…”
Section: Discussionmentioning
confidence: 99%